MAKNA DENOTASI DAN KONOTASI DALAM NOVEL ORANG-ORANG BIASA KARYA ANDREA HIRATA (KAJIAN SEMANTIK) - Ufitakh Zuhairoh (Pendidikan Bahasa dan Sastra Indonesia, 2022)
ABSTRACTAbstract: The most encountered linguistic environment in a novel is the use of denotation and connotation meanings. The novel of Orang-Orang Biasa is a novel with different attractions from the denotation and connotation meaning. This research aims to describe the denotation and connotation meaning of the novel. This research used the qualitative descriptive approach. The researcher collected the data with literature, reading, and noting techniques. Then, the researcher analyzed the obtained data by reducing, presenting, and concluding or verifying the data. The applied data validity consisted of the investigating triangulating stages. The triangulation process compared the works of an analyst with the other analyst. The finding descriptions showed 3 words of denotation meaning in the novel of Orang-Orang Biasa written by Andrea Hirata, (2) 3 words of connotation meaning in the novel of Orang-Orang Biasa written by Andrea Hirata.Keywords: Semantics, Denotation Meaning, Connotation Meaning, the Novel of Orang-Orang Biasa by Andrea HiratA